Clinical characteristics and health-related quality of life of patients with recurrent pericarditis in the United States: findings from a patient survey. (25th November 2020) - Lewinter, M; Kontzias, A; Lin, D; Cella, D; Dersarkissian, M; Totev, T; Duh, M.S; Lim-Watson, M; Magestro, M
Abstract: Background: Recurrent pericarditis (RP) is characterized by recurrence of symptoms of pericarditis after the original episode has ceased for 4–6 weeks. Though RP is associated with significant morbidity, there is little information regarding the impact of RP on patients' health-related quality of life (HRQOL). Purpose: To describe clinical characteristics of and HRQOL burden in patients with RP in the United States. Methods: An IRB-approved web-based survey was conducted among patients ≥18 years old with RP who experienced ≥1 recurrence during the prior 12 months. Respondents were recruited from the RHAPSODY clinical trial recruitment database. Patients who met the survey inclusion criteria were asked to provide information on their demographic/clinical characteristics, treatments for RP, and to complete an 11-point pericarditis pain numerical rating scale, the Patient Global Impression of Pericarditis Severity scale, the Patient-Reported Outcomes Measurement Information System® (PROMIS®) Global Health and Sleep Disturbance scales, and questions about the impact of RP on daily life. Results: Of the 83 respondents with RP included in the study, 25% responded while experiencing a recurrence. Most respondents were Caucasian (76%) and 55% were female, with mean (standard deviation [SD]) age of 49.3 (13.7) years. Patients frequently reported history of hypertension (39%), anxiety (37%), and depression (34%); 16% and 15% of patients reported having pre-existing autoimmune disease and diabetes, respectively. About half (49%) of patients reported ≥3 recurrences in the prior year, and 40% visited the ER and 25% were hospitalized for their most recent recurrence. Among patients not actively experiencing a recurrence, 37% reported that the duration of their prior episode lasted ≥8 days. Medications most frequently used for RP and pain in the prior year included non-steroidal anti-inflammatory drugs (82%), colchicine (63%), and corticosteroids (29%). Commonly reported symptoms included chest pain (93%), shortness of breath (66%), weakness/fatigue (64%), and heart palpitations (52%). Two-thirds of patients rated the severity of symptoms during the most recent RP episode as moderately severe to very severe, and 48% reported "quite a bit" or "very much" fear of pericarditis recurrence. The mean (SD) value for worst pericarditis pain (0–10 scale) during the recent recurrence was 6.1 (2.3), with 48% reporting severe pain (≥7 on the scale). Patients had substantially worse mean [SD] T scores for PROMIS physical health (37.6 [8.6]), mental health (42.8 [9.9]), and sleep disturbance (60.6 [8.3]) than the general population (50 [10]). Conclusions: RP is a burden on the daily lives of patients, resulting in severe pain and impaired quality-of-life including poor physical and mental health, sleep disturbance, and fear of recurrence. This study demonstrates the unmet need for therapies that can rapidly resolve symptoms and prevent recurrences. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Kiniksa Pharmaceuticals Corp.